A planimetric study of experimentally modeled infected wounds exposed to high-intensity pulsed broadband radiation - S. M. Chudnykh; V. S. Egorov; Kh. A. Abduvosidov; A. V. Snitsar; I. A. Chekmareva; A. Emaimo John (Biomedical Photonics)
An experimental model of an infected wound was created in 90 Wistar rats using a mixture of cultures of Staphylococcus aureus, Pseudomonas aeruginosa, Klebsiella pneumoniae, and Candida albicans. The animals are divided into 3 groups of 30 individuals. The first group consisted of animals treated with pulsed high-intensity broadband irradiation using an experimental apparatus with a pulsed xenon lamp operating in a pulsed periodic mode with an average UV-C (200-280 nm) radiation power of 3 W, and a pulsed UV-C power of 24 kW. In the second group, traditional ultraviolet irradiation of wounds with a mercury bactericidal lamp was used for treatment, with an average UV-C (254 nm) radiation power of 1.2 W. The third group received only a local antiseptic treatment. The computer planimetry was used for monitoring the effectiveness of treatment. Parameters such as wound area, rate, and degree of epithelialization were recorded on days 1, 7, 14, and 21 of treatment. The study showed that in the first group of animals, the rate and degree of epithelialization, as well as the reduction in wound area at each control stage, were statistically significantly greater compared to the use of traditional ultraviolet irradiation and local antiseptic monotherapy. This dynamic is associated with the earlier cleansing of wounds from pathogenic microorganisms and the morphological changes that correspond to an earlier transition from the inflammatory phase to the proliferation and regeneration phases. Therefore, the local treatment of infected wounds with antiseptic agents in combination with pulsed high-intensity wideband radiation promotes the earlier epithelialization of the wounds.